Behavioral and Psychological Phenotyping of Physical Activity and Sedentary Behavior: Implications for Weight Management. Issue 10 (26th September 2017) - Bryan, Angela D.; Jakicic, John M.; Hunter, Christine M.; Evans, Mary E.; Yanovski, Susan Z.; Epstein, Leonard H.
Abstract : Objective: Risk for obesity is determined by a complex mix of genetics and lifetime exposures at multiple levels, from the metabolic milieu to psychosocial and environmental influences. These phenotypic differences underlie the variability in risk for obesity and response to weight management interventions, including differences in physical activity and sedentary behavior. Methods: As part of a broader effort focused on behavioral and psychological phenotyping in obesity research, the National Institutes of Health convened a multidisciplinary workshop to explore the state of the science in behavioral and psychological phenotyping in humans to explain individual differences in physical activity, both as a risk factor for obesity development and in response to activity‐enhancing interventions. Results: Understanding the behavioral and psychological phenotypes that contribute to differences in physical activity and sedentary behavior could allow for improved treatment matching and inform new targets for tailored, innovative, and effective weight management interventions. Conclusions: This summary provides the rationale for identifying psychological and behavioral phenotypes relevant to physical activity and identifies opportunities for future research to better understand, define, measure, and validate putative phenotypic factors and characterize emerging phenotypes that are empirically associated with initiation of physical activity, response to intervention, and sustained changes in physical activity.